Administrasi Ketatausahaan di SD Negeri 100790 Situmbaga - Ade Safitri Siregar; Auliana Utamy; Dea Octavia Nasution; Yusmaini Yusmaini (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
This research aims to dig deeper into administrative practices at State Elementary School (SDN) 100790 Situmbaga. We adopted the interview method as the main tool to understand the perspectives and experiences of school operators in carrying out administrative tasks. The results of this interview provide an in-depth understanding of how school administration at SDN 100790 Situmbaga is carried out, including managing student data, school finances, coordinating activities, and communicating with stakeholders. Apart from that, this research also reveals the role of school information systems in facilitating administrative tasks and optimizing communication in schools. However, research also examines several obstacles faced by school operators, such as limited human resources, frequent changes in education policies, and increasing demands for reporting student achievement data and results. Therefore, this research provides important insights into the challenges faced in school administration and considers possible solutions to overcome these obstacles.